2018
DOI: 10.1177/1533033818787377
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Prostate Health Index (PHI) to Predict Gleason Score in Patients With Prostate Cancer and Discriminate Patients Between Gleason Score 6 and Gleason Score Higher Than 6—A Study on 320 Patients After Radical Prostatectomy

Abstract: Aim:The purpose of this study was to investigate the Prostate Health Index as a marker for tumor aggressiveness in prostate biopsy and the optimization of indication for treatment options.Methods:Our cohort consisted of 320 patients indicated for radical prostatectomy with preoperative measurements of total prostate-specific antigen, free prostate-specific antigen, [-2]proPSA, calculated %freePSA, and Prostate Health Index. The Gleason score was determined during biopsy and after radical prostatectomy. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Prostate cancer antigen 3 (PCA3, prostate-specific non-coding mRNA) is involved in the biomarker set. The detection is performed in urine based on the prostate massage approach releasing biomarkers to urine [ 165 , 166 ].…”
Section: Concluding Remarks and 3pm Related Outlookmentioning
confidence: 99%
“…Prostate cancer antigen 3 (PCA3, prostate-specific non-coding mRNA) is involved in the biomarker set. The detection is performed in urine based on the prostate massage approach releasing biomarkers to urine [ 165 , 166 ].…”
Section: Concluding Remarks and 3pm Related Outlookmentioning
confidence: 99%
“…In a recently published study [39], the authors showed that phi is the most accurate predictor (AUC 0.74 [0.68-0.80] of definitive Gs higher than 6. This is particularly relevant since a Gs ≤ 6 is one of the criterion used for the selection of patients for AS, suggesting that phi could be advantageous to choose the best treatment option.…”
Section: Radical Prostatectomymentioning
confidence: 99%
“…PHI values were compared with definitive staging and grading. The study confirmed a very good ability of PHI to distinguish GS < 7 (low aggressiveness) and GS ≥ 7 (higher aggressiveness) prostate tumors and thus, PHI was added to the first line of biochemical assessment of the tumor aggressiveness [ 5 ].…”
Section: Diagnostic Algorithmmentioning
confidence: 65%